e-auction / Chiang Ming Jen - Chiang , Ming Jen (2004)
This study of project is the fulfillment for WXES 3181. The entire project, maned e-Auction. involves developing a web based interaction system for the use of the public or company. This system will be built in a simple high quality and fast way by using certain tools. The objective for developing this e-Auction System is to dynamic pricing marketplace for short life cycle and unique products by delivering maximum value for suppliers and buyers. This system also will include user friendly feature. In consideration of providing these advance features, Active Server Pages 3.0 has been chosen as the developing language, with database support by Microsoft SQL server 2000, in the platform of Windows 200, running with server IIS. With reference and review from the other systems, the additive enhancement of features and cautious consideration of the existing constraint in bidding environment, is expectedly leading this project to the future implementation.